Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
x = -6
Step-by-step explanation:
You can insert the second equation in for the y-variable in the first equation
x + 4(2x+14) = 2
The next step is to distribute the 4
x + 8x + 56 = 2
Then we combine like terms
9x + 56 = 2
Subtract 56 from both sides
9x = -54
Divide by 9 on both sides
x = -6
Answer:
x = - 6; y = 2
Step-by-step explanation:
{x + 4y = 2
{y = 2x + 14
x = 2 - 4y
y = 2x + 14
y = 2(2 - 4y) + 14
y = 4 - 8y + 14
y + 8y = 14 + 4
9y = 18
y = 18/9
y = 2
x = 2 - 4y
x = 2 - 4×2
x = 2 - 8
x = - 6
I hope I've helped you.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.